Territorial Innovative Potential in Behavioral Assessments of the Population - Tatarkin, Aleksandr Ivanovich; Novikova, Ksenia Alexandrovna (Economy of Regions, 2015)
In the article, the essential and formalized definition of the potential of the territory is proved; its innovative part in the “subject- process-object” approach to its essential content and impact assessment is determined. The system of mechanisms and institutes of building the regional and territorial innovative potential is elaborated, the most productive directions of its using in the interests of spatial socio-economic development are allocated. Problems of high priority and requiring solutions that are able to increase the effectiveness of territory functioning are identified. The mentioned problems found their reflection and possible solutions at the Gaidar International Economic Forum in Moscow (2015) and at the representative XII Krasnoyarsk Economic Forum, as reflected by the analyses of some forum’s speeches presented in the paper. The shift of priorities in innovative global development during the second part of the 20th century and at the beginning of the 21st century is shown. The results of research and practice of utilizing innovative solutions for the development of some collectives and territories, the spatial structure of regions and the Russian Federation as a whole are investigated and generalized in this paper. The development of the territory and its potential depends on different factors, but the growth of knowledge, intellectual resource and involvement of the population into management process by development and realization of different programs and projects plays the increasing role in current conditions. In the article, the positive sides of the business-project as the main mechanism of the program and project implementation with utilizing market institutes of the public-private partnership (PPP) are analyzed. The role of collectives and the population in the increase of innovative activity and system territory development is assessed.